2002
DOI: 10.1007/s00253-002-1074-9
|View full text |Cite
|
Sign up to set email alerts
|

Microbial community changes during organic solid waste treatment analyzed by double gradient-denaturing gradient gel electrophoresis and fluorescence in situ hybridization

Abstract: The bacterial community present during semicontinuous treatment of organic solid waste under alkaline and high-temperature conditions was studied. PCR-amplified 16S rDNA fragments were analyzed by double gradient-denaturing gradient gel electrophoresis (DGGE). The band pattern was stable during the steady state of the treatment phase, and the major bands resulting from individual treatments had the same DNA sequence with good reproducibility. No sequence in the DNA database of isolated bacteria showed close si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Sterile nylon cloth was used for filtering out the supernatant from the biomass pulp, which was later dried at 55°C for 48 h, and the supernatants (BPS-E4 and BPS-E87) were used as crude enzyme solutions, which were obtained from the BPS-D2 and BPS-M2 treatments, respectively. The relative dry weight (RDW) was calculated, with the alkali pretreated sample (BPS-G104a) serving as the control [1, 35]. …”
Section: Methodsmentioning
confidence: 99%
“…Sterile nylon cloth was used for filtering out the supernatant from the biomass pulp, which was later dried at 55°C for 48 h, and the supernatants (BPS-E4 and BPS-E87) were used as crude enzyme solutions, which were obtained from the BPS-D2 and BPS-M2 treatments, respectively. The relative dry weight (RDW) was calculated, with the alkali pretreated sample (BPS-G104a) serving as the control [1, 35]. …”
Section: Methodsmentioning
confidence: 99%
“…b Changing of the maximum temperature (°C) and DGGE band patterns in the sample during the operation mixed composting reactor. DGGE is a powerful tool to analyze easily and rapidly the diversity of and changes in a microbial community (Muyzer et al 1993;Haruta et al 2002). However, it could not detect some species of the minor population, which may also have played an important role.…”
Section: Discussionmentioning
confidence: 99%
“…Dees and Ghiorse showed that Brevibacillus borstelensis, Aneurinibacillus thermoaerophilus, Bacillus coagulans, Bacillus licheniformis, and Weissella confusa were detected from a small-scale (30 L) composting reactor to which dog food was added (Dees and Ghiorse 2001). Haruta et al (2002) showed that Bacillus thermoamylovorans and Ureibacillus thermosphaericus were detected as 40% of the total bacterial cells on day 5, while Cerasibacillus quisquiliarum accounted for 30% on day 9 from a small-scale (30 L) composting reactor. Bacillus thermocloacae, Bacillus licheniformis, and Clostridium ultunense were also detected from this reactor in which the daily garbage from a family kitchen was added to simulate the composting reaction.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The group of eubacteria, archaea and methanogen can be distinguished with different labeled probes (Hill et al, 2000). The oligonucleotide probes (EUB338) used in this study has been shown to detect almost all eubacteria (Haruta et al, 2002). Drying touch preparations in air, locus-specific probe specificity and chemical composition of cell were the major contribution to autofluorescence (Szollosi et al, 1995;Ainsworth et al, 2006).…”
Section: Discussionmentioning
confidence: 99%